2022
DOI: 10.1186/s12916-022-02677-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of Escherichia coli: antimicrobial resistance through a One Health lens in sympatric humans, livestock and peri-domestic wildlife in Nairobi, Kenya

Abstract: Background Livestock systems have been proposed as a reservoir for antimicrobial-resistant (AMR) bacteria and AMR genetic determinants that may infect or colonise humans, yet quantitative evidence regarding their epidemiological role remains lacking. Here, we used a combination of genomics, epidemiology and ecology to investigate patterns of AMR gene carriage in Escherichia coli, regarded as a sentinel organism. Methods We conducted a structured ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…There was no relationship between DEC carriage and number of household members which has been identified in previous studies as a risk factor together with animal feces/ manure within the premises [53,54]. Livestock keeping is a common practice in this rapidly urbanizing environment, and interactions between children and livestock is possible even with non-livestock keeping households [29,54,55]. However, there was consistence that livestock ownership had no association with DEC carriage.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There was no relationship between DEC carriage and number of household members which has been identified in previous studies as a risk factor together with animal feces/ manure within the premises [53,54]. Livestock keeping is a common practice in this rapidly urbanizing environment, and interactions between children and livestock is possible even with non-livestock keeping households [29,54,55]. However, there was consistence that livestock ownership had no association with DEC carriage.…”
Section: Discussionmentioning
confidence: 75%
“…This could have been due to fecal shedding that results in lower pathogen positivity as diarrhea subsides and microbiota-mediated pathogen clearance [52]. There was no relationship between DEC carriage and number of household members which has been identified in previous studies as a risk factor together with animal feces/ manure within the premises [53,54]. Livestock keeping is a common practice in this rapidly urbanizing environment, and interactions between children and livestock is possible even with non-livestock keeping households [29,54,55].…”
Section: Discussionmentioning
confidence: 87%
“…In Poland, Katherine et al, 18 in a study done on children complaining from gastroenteritis reported that E. coli O157:H7 serotype was not isolated at all. Similarly, Muloi et al 19 could not isolate E. coli O157:H7 from any of 606 diarrhea cases in Italy.…”
Section: Discussionmentioning
confidence: 95%
“…To address the increasing prevalence of MDR E. coli infections in humans, it is essential to gain insights into the reservoirs and origins from which humans acquire these infections. A combination of WGS, epidemiology, and ecology was employed to investigate the prevalence of AMR carriage and to characterise the diversity of AMR genes in E. coli, in Nairobi, Kenya [173]. The study pointed out that the composition of AMR gene communities was not linked to the host species.…”
Section: One Health Genomics and Perspectivesmentioning
confidence: 99%